Simplification of Validated Patient-Reported Outcome Instruments in Inflammatory Bowel Disease. Issue 3 (6th December 2019) - Andersen, Michael J; Yvellez, Olivia V; El Jurdi, Katia; Sossenheimer, Philip H; Lei, Donald; Pearl, Talia A; Zmeter, Nada; Rubin, David T
Abstract: Objectives: Improving health-related quality of life (HRQoL) is a major treatment goal for inflammatory bowel disease (IBD) patients. Tools to measure HRQoL, including the Pittsburgh Sleep Quality Index and the Short Inflammatory Bowel Diseases Questionnaire, are lengthy and rely on recall. This prospective, proof-of-concept pilot study assessed the feasibility, reliability, and validity of daily, simplified HRQoL and sleep quality data collection using mobile technologies in patients with IBD. Methods: Adult IBD patients were recruited from our center. Daily HRQoL and sleep quality were assessed using visual analog scale (VAS) surveys, and pain was assessed using the Wong-Baker FACES Pain Rating Scale (WBS). HRQoL and sleep were assessed on days 1, 14, and 28 of the study using the short IBD Questionnaire (SIBDQ) and Pittsburgh Sleep Quality Index (PSQI). Correlation between the daily instruments and the biweekly validated instruments were assessed using the Pearson correlation coefficient. Results: One hundred patients were enrolled. The correlation between mean global assessment VAS score over 2 weeks and PSQI score taken at 14 days was moderate ( r = 0.62, P < 0.0001). The correlation over the same time interval between mean WBS score and SIBDQ score was strong ( r = −0.71, P < 0.0001), and the correlation between mean sleep VAS score and PSQI score was moderate ( r = −0.55, P < 0.0001). Conclusions: This study demonstrates the potential for electronic quality of life, sleep quality, and pain assessments as feasible, reliable, and valid tools in IBD patients. Intermittent administration of these simplified electronic assessments may be useful in further reducing patient survey burden without significantly compromising their utility. Lay Summary: Measurement of health-related quality of life, sleep quality, and pain in IBD patients is clinically important, but validated instruments are burdensome, subjective, and retrospective. We demonstrate the feasibility of simplified, electronic measures and their correlation with previously validated measures.